The prognostic significance of primary tumor laterality in malignant ovarian teratomas: a 10-year experience at a single institution - Ji, Xuechao; Zheng, Zian; Yang, Jing; Li, Guoliang; Liu, Xiangyu (Frontiers in Immunology, 2026)
BackgroundApproximately 95% of ovarian teratomas are classified as benign, with only about 5% being malignant. Nevertheless, no research has previously explored the connection between primary tumor laterality and prognostic outcomes among malignant ovarian teratoma (MOT) patients. Our aim was to investigate the association of primary tumor laterality with prognosis in MOT.MethodsThis retrospective study enrolled patients with MOT from The Affiliated Hospital of Qingdao University from January 2012 to December 2021. The primary outcome was progression-free survival (PFS) and overall survival (OS). The prognostic difference between left-sided, right-sided and bilateral groups was investigated using Kaplan-Meier analyses and Cox proportional hazards regression analyses.ResultsA total of 51 eligible patients with MOT were included with a median age of 52 years. Among the patients with MOT, the multivariate Cox regression analyses showed that right-sided (hazard ratio [HR]=0.01; 95% confidence interval [CI]=0.00-0.04; P = 0.01) MOT was associated with better PFS, compared with left-sided MOT (HR = 1.00). Kaplan-Meier analyses also showed that the primary tumor laterality had a significant prognostic effect in MOT.ConclusionAmong patients with MOT, those with unilateral tumors, particularly right-sided ones, had a significantly better prognosis than those with bilateral tumors. Gynecologic oncologists might account for the prognostic impact of primary tumor laterality in MOT and tailor treatment and surveillance accordingly.